Utilization of leaf and fruit extracts of kedondong (Spondias dulcis Forst) as a supporting material for energy conversion in dye sensitized solar cells and electrochemical cells - Agus Malik Ibrahim; Boima Situmeang; Ahmad Rifa’i; Afif Hidayatul Mustafid (Jurnal Pendidikan Kimia (JPKim), 2021)
This study aims to obtain a dye sensitized solar cell (DSSC) prototype and a voltaic cell prototype using the kedondong plant (Spondias dulcis Forst). Kedondong leaves as a source of chlorophyll were deliberately chosen to be in line with the use of kedondong fruit as a material for electrochemical cells, so that two research results could be obtained from the kedondong plant. This research is for the application of scientific development, increasing the added value of kedondong plant, and as support for the use of environmentally friendly energy. Research methods in general are chlorophyll extraction, citric acid isolation, chlorophyll testing, DSSC assembly, electrochemical cell assembly, and performance testing for both DSSC and electrochemical cells. The analysis results show that typical peaks appear for the functional groups in chlorophyll at certain wave numbers. Hydroxyl (-OH) groups appear in the range of 3650 - 3200 cm-1, the C=C group at 1700 - 1500 cm-1, the C-N group at 1350 - 1000 cm-1, and the C-O group at 1300 - 1000 cm-1. Quantitative testing used a UV-Vis spectrophotometer at 645 nm and 633 nm, the results obtained were chlorophyll a was 4.52 mg/L, chlorophyll b was 8.43 mg/L, and total chlorophyll was 12.95 mg/L. The DSSC prototype performance test with a size of only 2.5 cm2, can produce a minimum voltage of 30.1 mV and a maximum of 280 mV. The electrochemical test of kedondong citric acid extract showed that the value of the electric voltage ranged from 121 to 630 mV.Keywords: Kedondong, Chlorophyll, DSSC, Citric acid, Electrochemical cells